2010
DOI: 10.1024/1661-4747/a000017
|View full text |Cite
|
Sign up to set email alerts
|

Was passiert nach der stationären Stabilisierung mit komplex traumatisierten PTB-Patientinnen?

Abstract: Bei Patienten mit Posttraumatischen Belastungsstörungen (PTB) und zusätzlicher komplexer Thematik erfolgt in Deutschland im stationären Setting überwiegend eine Stabilisierung. Angenommen wird dabei, dass die erfolgreich Stabilisierten in einer ambulanten Folgetherapie mit einem traumakonfrontativen Verfahren behandelt werden. Die hier vorliegende Arbeit hat zwei Ziele: Erstens soll eine quantitative Literaturübersicht zum Thema Stabilisierung und Konfrontation bei komplex Traumatisierten gegeben werden. Hier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…The authors reviewed the existing literature and argued that the research on stabilization is based on methodologically limited studies and that there is no clear evidence for a stabilization phase prior to the use of confrontational methods. Concerning this debate, one has to keep in mind that the term “stabilization” is not clearly defined: It is likely that stabilization describes different methods, procedures and therapy goals in different articles (63). In our treatment, stabilization included psychoeducation about the disorder, stress management and distancing methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reviewed the existing literature and argued that the research on stabilization is based on methodologically limited studies and that there is no clear evidence for a stabilization phase prior to the use of confrontational methods. Concerning this debate, one has to keep in mind that the term “stabilization” is not clearly defined: It is likely that stabilization describes different methods, procedures and therapy goals in different articles (63). In our treatment, stabilization included psychoeducation about the disorder, stress management and distancing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, patients reported that talking about symptoms, etiology and relating factors was important to understand their disorder and symptoms. Many authors (30, 63, 69) highlight that it is necessary to also report adverse effects or deterioration after therapy. Another reason for the increase in somatoform symptoms and stagnation in PTSD symptoms is that our patients reported a very high extent of somatoform symptoms (M = 13.70) compared to the findings from Gräfe and colleagues (70; M = 6.4, 9.8, 9.7 for patients without psychiatric disorder, with psychiatric comorbidity and those in psychosomatic treatment, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Dies bedeutet im Umkehrschluss, dass bei rund 30% der PTBS-Fälle keine leitlinienkonforme ambulante Psychotherapie in den Therapieplänen der Berichte an den Gutachter beschrieben wurde. Im Vergleich zu früheren Studien [Rosner et al, 2010;Kröger et al, 2010], in denen noch weitaus niedrigere Werte für den Einsatz traumafokussierter Psychotherapie (13% bzw. 30%) nachgewiesen werden konnten, ist der in der vorliegenden Studie erfasste Wert von rund 70% noch relativ hoch.…”
Section: Diskussionunclassified
“…Kognitive Therapien, expositionsbasierte Therapien und Eye Movement Desensitization and Reprocessing (EMDR) erwiesen sich dabei als wirksame Behandlungsmethoden [Watts et al, 2013] [Becker et al, 2004]. Die Folge ist, dass diese Patientinnen oft behandelt werden, ohne je gezielt über die Traumaerfahrungen zu sprechen [Rosner et al, 2010].…”
Section: Therapieansätze Und Leitlinien Zur Behandlung Der Ptbsunclassified